2012
DOI: 10.1111/j.1948-7134.2012.00205.x
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of hantaviruses in small wild mammals trapped in South Korea from 2005 to 2010

Abstract: The seroprevalence of Hantaan virus (HTNV) in wild rodents in South Korea was analyzed. Wild rodents were trapped in 18 cities in eight provinces during 2005-2007 and on three islands and four mountains during 2008-2010. Sera were collected from 629 out of 933 trapped wild animals and examined for immunoglobulin G antibodies to HTNV using indirect immunofluorescence assays. Apodemus agrarius (80.1%) was the most frequently captured species at almost all trapping sites. The overall prevalence of HTNV antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…There are more Hantavirus-infected rodents in the autumn than there are during other seasons of the year [44, 45]. Seasonally, there are two peaks in the antibody prevalence in striped field mice in April and between September and December.…”
Section: Discussionmentioning
confidence: 99%
“…There are more Hantavirus-infected rodents in the autumn than there are during other seasons of the year [44, 45]. Seasonally, there are two peaks in the antibody prevalence in striped field mice in April and between September and December.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous report, an almost identical pattern of HFRS incidence was identified in soldiers in endemic areas (7). Higher incidence of HFRS in the autumn, versus other seasons, could be attributed to the high numbers of hantavirus-infected rodents in Korea during this time (10, 11). Seroprevalence of hantaviruses in wild rodents in Korea confidently demonstrated that most wild rodent hantavirus infections occur in the autumn.…”
mentioning
confidence: 98%
“…However, the seroprevalence and infection of hantavirus in rodent and human populations of East Malaysia are still largely unknown. There were also several reported cases of rodents infected with hantavirus in neighbouring countries [i.e., China (Lin et al 2012;Wang et al 2000), South Korea (Lim et al 2012), Singapore (Wong et al 1985(Wong et al ,1988Johannson et al 2010), Indonesia (Plyusnina et al 2009;Ibrahim et al 2013), Thailand, Cambodia and Lao PDR (Nitatpattana et al 2000;Reynes et al 2003;Blasdell et al 2011Blasdell et al , 2016], which suggested that there was a possibility for the circulation of hantavirus in the rodent populations in East Malaysia.…”
mentioning
confidence: 99%